Decision-Making of Patients With Implantable Cardioverter-Defibrillators at End of Life: Family Members' Experiences. (July 2017) - Lee, Mei Ching; Sulmasy, Daniel P.; Gallo, Joseph; Kub, Joan; Hughes, Mark T.; Russell, Stuart; Kellogg, Anela; Owens, Sharon G.; Terry, Peter; Nolan, Marie T.
Introduction: Many patients with advanced heart failure (HF) experience the life-extending benefits of implantable cardioverter-defibrillators (ICD), but at the end stage of HF, patients may experience shocks with increasing frequency and change the plan for end-of-life (EOL) care including the deactivation of the ICD. This report describes family members' experiences of patients with ICD making decisions at EOL. Understanding the decision-making of patients with ICD at EOL can promote informed decision-making and improve the quality of EOL care. Methods: This pilot study used a mixed methods approach to test the effects of a nurse-guided discussion in decision-making about ICD deactivation (turning off the defibrillation function) at the EOL. Interviews were conducted, audiotaped, and transcribed in 2012 to 2013 with 6 family members of patients with advanced HF and ICDs. Three researchers coded the data and identified themes in 2014. Results: Three main themes described family members' experiences related to patients having HF with ICDs making health-care decision at EOL: decision-making preferences, patients' perception on ICD deactivation, and communication methods. Discussion: Health-care providers need to have knowledge of patients' decision-making preferences. Preferences for decision-making include the allowing of appropriate people to involve and encourages direct conversation with family members even when advance directives is completed. Information of ICD function and the option of deactivation need to be clearly delivered to patients and family members. Education and guidelines will facilitate the communication of the preferences of EOL care.